2021
DOI: 10.31674/mjn.2021.v13i01.010
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Knowledge and Attitude Towards Patient Safety Among Nursing Students in Private College

Abstract: Background: Patient safety is defined as the absence of preventable harm to a patient while providing health care, as well as the reduction of unnecessary harm associated with health care. The delivery of better healthcare requires the protection of patients. It is crucial to evaluate nursing students' knowledge and attitudes toward patient safety to identify deficiencies in the educational curriculum and encourage students in patient safety activities. Given the importance of patient safety today, the purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
0
0
1
Order By: Relevance
“…When compared to students in their third year of study, those in their fourth or higher year of study showed better patient safety practices. The results of this study corroborate with prior studies' findings that greater nurse education levels are associated with better patient safety practices and outcome ( 26 , 27 ). A possible explanation would be that students in their fourth and higher years spend more time in clinical attachments overall, which could boost their level of experience and practice.…”
Section: Discussionsupporting
confidence: 88%
“…When compared to students in their third year of study, those in their fourth or higher year of study showed better patient safety practices. The results of this study corroborate with prior studies' findings that greater nurse education levels are associated with better patient safety practices and outcome ( 26 , 27 ). A possible explanation would be that students in their fourth and higher years spend more time in clinical attachments overall, which could boost their level of experience and practice.…”
Section: Discussionsupporting
confidence: 88%
“…Tuy nhiên, kết quả nghiên cứu của chúng tôi thấp hơn so với một số nghiên cứu. Một nghiên cứu thực hiện năm 2021 tại Malaysia với 92 sinh viên điều dưỡng năm cuối tham gia khảo sát, kết quả đánh giá cho thấy rằng có đến 98,9% sinh viên có kiến thức tốt [7]. Tương tự, nghiên cứu thực hiện tại Kajang, Malaysia nhằm đánh giá kiến thức của điều dưỡng về an toàn người bệnh cho thấy rằng 96,9% điều dưỡng có kiến thức tốt, chỉ có 3,1% điều dưỡng có kiến thức chưa tốt về an toàn người bệnh [1].…”
Section: Kiến Thức Về An Toàn Người Bệnh Của Sinh Viên đIều Dưỡng Và ...unclassified